Polymorphisms in Plasmodium falciparum K13-Propeller in Angola and Mozambique after the Introduction of the ACTs. - Escobar, C (2015)
We report the presence of SNPs in Plasmodium falciparum K13-propeller gene in two African countries, Angola and Mozambique, where malaria is a serious public health problem. Samples were collected before and after ACT introduction as first-line treatment. In each country 50 samples collected before and 50 after ACT introduction were analysed. A total of three different mutations (R471R and R575R in Angola and V494I in Mozambique) were identified in five samples, all collected after the introduction of ACT. The R471R mutation detected in Angola has already been reported in Africa (DR-Congo and Gabon). However, the mutations R575R (Angola) and V494I (Mozambique), have never been reported. V494I is adjacent to the known K13 resistance-associated mutation Y493H, although functional analysis did not predict a deleterious effect on protein function.